Ted, Bo, and Diz : the first adventure - Chapman, Jason (Intercourse, PA : Good Books, 2007)
Friends Ted, Bo, and Diz encounter a family of polar bears while on an ocean adventure and help them find safety when their iceberg begins to melt.
Original edition published in English by Little Tiger Press, London, England, 2007.
Kirkus Review.
2.7
K-3
Keywords: Beaches -- Fiction; Bears -- Fiction; Ocean -- Fiction; Polar bears -- Fiction; Seals -- Fiction; Beaches -- Fiction; Bears -- Fiction; Ocean -- Fiction; Polar bears -- Fiction; Seals -- Fiction